(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
A Proposed device designed to protect the crops not only from the birds but also it is equipped with the multiple sensors to sense and repel the wild animals also from the cropland. It is also designed to sense any kind of fire around the cropland. It can also sense the moisture level of soil and alarm the farmers about it if moisture level goes down or high. In this research paper we have done an experiment to check the effect of temperature on this device. We have kept this device under various environments with different temperature and keep on observing it 24 hours. This DIEL cycle of 24 hours in various temperatures shows the effects of temperature on this designed model. We have clearly found out the effects of temperature on this device and can work efficiently in our region. We can also extend this experiment in various regions of country also. For this experiment, we have chosen our local area of Ara, Bihta and Patna. We have tried to find out the difficulties in working environment of this device.